Penerapan Prinsip Efisiensi Dalam Pengelolaan Dana BOS dan BPP di SMK Negeri 2 Palangka Raya - Aan Mirkan; Yefta Yefta; Mersi Faot; Yulika Yulika; Feronika S.Y (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2026)
This study analyzes the implementation of efficiency principles in the management of School Operational Assistance (BOS) funds and Education Operational Costs (BPP) at SMK Negeri 2 Palangka Raya. A descriptive qualitative approach was employed with purposive sampling. Research informants comprised the BOS treasurer, BPP secretary, school principal, ARKAS operator, and school committee chairperson. Data were gathered through in-depth interviews, non-participant observation, and documentation, then analyzed using the Miles, Huberman, and Saldana model through three stages: data reduction, data display, and conclusion drawing. Findings reveal that fund management has broadly complied with the provisions of Ministry of Education Regulation Number 63 of 2022 as amended by Regulation Number 63 of 2023, encompassing ARKAS-based planning, phased disbursement, financial administration, supervision, and periodic reporting. Nevertheless, persistent challenges were identified, namely delayed BOS fund disbursement, insufficient accounting expertise among staff, suboptimal integration of digital financial systems, and the absence of objective budget-priority instruments. This study offers a distinctive contribution by examining the integrated management of BOS and BPP funds within vocational schools characterized by practice-based learning and elevated operational costs.